External evaluation in municipal level: The impacts of an experience - Ferrarotto, Luana; Malavasi, Maria Márcia Sigrist (Revista Eletrônica de Educação, 2015)
<!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> DOI: http://dx.doi.org/10.14244/198271991476 The external evaluation is a consolidated reality in our country. Besides the state and federal ones, there are some municipalities that develop their own evaluation programs. To contribute with the debate about the external evaluations, this article presents data from a research which aim was to identify the actions from the Educational Secretariat from a city in the State of São Paulo, Brazil, opposite to the results of PROMASE (Municipal Assessment of the Educational System) and its impact in school’s units. It is still being analyzed the path taken by the program with the aim of explaining its conception of the teaching quality. This way, the qualitative research was chosen based on the interviews with the Educational Secretary, teachers and school’s managers. Accordingly with the Secretary, after PROMASE, actions since improvements in the buildings to curricular restructuring and continuing educational were made. Even without the rankings and performance payments, it is noticeable in schools the built of what is called “hidden” and “adjustment” rankings of the pedagogical and evaluative practices to the matrix and to the evaluative instrument of the program to improve the teaching quality and improve the index. For an evaluative system to bring contributions to the network, it is noticeable that the quality must be anchored to the social quality, which more than the index, establishes its own scale as a protagonist in the process of looking to itself, adverse to the blaming of the teachers for the standards tests results and that, consequently, favors the social, political, cultural and human formation of the students. Keywords: External evaluation, Evaluation on municipal level, Teaching quality. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->